2020
DOI: 10.1159/000509747
|View full text |Cite
|
Sign up to set email alerts
|

Major Durable Response of Pembrolizumab in Chemotherapy Refractory Small Cell Bladder Cancer: A Case Report

Abstract: Small cell carcinoma of the urinary bladder is a rare subtype (incidence of 1–9/1,000,000), characterized by an aggressive behavior with early metastasis and poor prognosis. Chemotherapy, radiation, and surgery are the usual treatment options, but to date, no accepted standard treatment exists. Since small cell bladder cancer shares similar clinicopathological features with small cell lung cancer, the same type of chemotherapy has been used. Recently, immune checkpoint inhibitors have shown effect in small cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A phase II study of nivolumab and ipilimumab for patients with advanced rare genitourinary malignancies demonstrated responses in 7 out of 19 patients, with responses observed in 2 of 3 patients with GSCC (one with CR) [ 17 ]. Several case reports were published also showing good responses to ICIs in patients with SCCB [ 18 20 ]. In accordance with the results mentioned above, our study also found that GSCC was associated with superior survival outcomes when adding immunotherapy to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A phase II study of nivolumab and ipilimumab for patients with advanced rare genitourinary malignancies demonstrated responses in 7 out of 19 patients, with responses observed in 2 of 3 patients with GSCC (one with CR) [ 17 ]. Several case reports were published also showing good responses to ICIs in patients with SCCB [ 18 20 ]. In accordance with the results mentioned above, our study also found that GSCC was associated with superior survival outcomes when adding immunotherapy to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 (programmed cell death protein 1) and PD-L1 (programmed death-ligand 1) inhibitors have also been tested in this disorder, and although they have generally not been successful, positive results have been described in case reports. Clinical trials with adequate evidence are ongoing [11,[30][31][32].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Based on these observations, a role of checkpoint inhibitors for NEC of the bladder was hypothesized. Although direct experience with bladder LCNEC is nearly absent so far, results obtained in few patients with SCNEC of the urinary system are promising and could lead to new treatment option for patients affected by this rare malignancy [67][68][69]. Moreover, investigating targetable genomic alterations in these patients may help improve their multimodal treatment [6,[70][71][72].…”
Section: Future Perspectivesmentioning
confidence: 99%